2016
DOI: 10.3171/2015.8.spine15219
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent surgery rates after cervical total disc replacement using a Mobi-C Cervical Disc Prosthesis versus anterior cervical discectomy and fusion: a prospective randomized clinical trial with 5-year follow-up

Abstract: OBJECTIVE Cervical total disc replacement (TDR) has been shown in a number of prospective clinical studies to be a viable treatment alternative to anterior cervical discectomy and fusion (ACDF) for the treatment of symptomatic degenerative disc disease. In addition to preserving motion, evidence suggests that cervical TDR may result in a lower incidence of subsequent surgical intervention than treatment with fusion. The goal of this study was to evaluate subsequent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 34 publications
2
37
1
Order By: Relevance
“…P-tau proteins are key components of neurofibrillary tangles in epilepsy (35). Previous research has also reported that excessive p-tau protein is related to cognitive impairment in Alzheimer's disease (37). In the present study, it was demonstrated that geniposide attenuates GSK-3β protein expression in mice epilepsy.…”
Section: Discussionsupporting
confidence: 54%
“…P-tau proteins are key components of neurofibrillary tangles in epilepsy (35). Previous research has also reported that excessive p-tau protein is related to cognitive impairment in Alzheimer's disease (37). In the present study, it was demonstrated that geniposide attenuates GSK-3β protein expression in mice epilepsy.…”
Section: Discussionsupporting
confidence: 54%
“…The cohort in this study was followed for at least 5 years with a follow-up of 94% and showed a statistically significant difference in rates of reoperations in total, advantageous for ACDF. This finding is deviant to results from most previously published RCTs and meta-analyzes showing lower rates of reoperations in the ADR groups [34][35][36][37][38]. The results in our study are supported by a study presented by Nandyala et al in 2014.…”
Section: Discussioncontrasting
confidence: 51%
“…The decision for subsequent surgical intervention was determined solely by the treating surgeon and the patient's personal decision to proceed. Consistent with other analyses, 9,11,15,18 index-level secondary surgeries were categorized when possible as a revision, removal, reoperation or supplemental fixation. Essentially, any surgery that touched the index level was considered as an index-level reoperation, even if the primary goal of surgery was to correct an adjacent level problem.…”
Section: Primary Success Endpointmentioning
confidence: 96%
“…13,15,24,25 The study protocol did not specify the indications for reoperation in either treatment group. The decision for subsequent surgical intervention was determined solely by the treating surgeon and the patient's personal decision to proceed.…”
Section: Primary Success Endpointmentioning
confidence: 99%
See 1 more Smart Citation